Cactus hotel - Guiberson, Brenda Z.; Lioyd, Megan (Paris L'école des loisirs, 1996)
Describes the life cycle of the giant saguaro cactus, with an emphasis on its role as a home for other desert dwellers.
Keywords: Saguaro -- Juvenile literature; Desert ecology -- Sonoran Desert -- Juvenile literature